MR-Guided Radiotherapy for Head and Neck Cancer: Current Developments, Perspectives, and Challenges - Boeke, Simon; Mönnich, David; van Timmeren, Janita E.; Balermpas, Panagiotis (Frontiers in Oncology, 2021)
Based on the development of new hybrid machines consisting of an MRI and a linear accelerator, magnetic resonance image guided radiotherapy (MRgRT) has revolutionized the field of adaptive treatment in recent years. Although an increasing number of studies have been published, investigating technical and clinical aspects of this technique for various indications, utilizations of MRgRT for adaptive treatment of head and neck cancer (HNC) remains in its infancy. Yet, the possible benefits of this novel technology for HNC patients, allowing for better soft-tissue delineation, intra- and interfractional treatment monitoring and more frequent plan adaptations appear more than obvious. At the same time, new technical, clinical and logistic challenges emerge. The purpose of this article is to summarize and discuss the rationale, recent developments and future perspectives of this promising radiotherapy modality for treating HNC.